Uncertainty analysis of quantitative imaging features extracted from contrast-enhanced CT in lung tumors. (March 2016) - Yang, Jinzhong; Zhang, Lifei; Fave, Xenia J.; Fried, David V.; Stingo, Francesco C.; Ng, Chaan S.; Court, Laurence E.
Highlights: Quantitative imaging features had little dependency on the time after contrast injection. Most quantitative imaging features were reproducible between scanning sessions several days apart. Some texture features changed gradually after contrast injection but eventually became stable. Imaging noise had little impact on texture features. Compact prognostic features could be derived from calculated redundant features. Abstract: Purpose: To assess the uncertainty of quantitative imaging features extracted from contrast-enhanced computed tomography (CT) scans of lung cancer patients in terms of the dependency on the time after contrast injection and the feature reproducibility between scans. Methods: Eight patients underwent contrast-enhanced CT scans of lung tumors on two sessions 2–7 days apart. Each session included 6 CT scans of the same anatomy taken every 15 s, starting 50 s after contrast injection. Image features based on intensity histogram, co-occurrence matrix, neighborhood gray-tone difference matrix, run-length matrix, and geometric shape were extracted from the tumor for each scan. Spearman's correlation was used to examine the dependency of features on the time after contrast injection, with values over 0.50 considered time-dependent. Concordance correlation coefficients were calculated to examine the reproducibility of each feature between times of scans after contrast injection and between scanning sessions, with values greater than 0.90 considered reproducible. Results: The features were found to have little dependency on the time between the contrast injection and the CT scan. Most features were reproducible between times of scans after contrast injection and between scanning sessions. Some features were more reproducible when they were extracted from a CT scan performed at a longer time after contrast injection. Conclusion: The quantitative imaging features tested here are mostly reproducible and show little dependency on the time after contrast injection.